THE EFFECTIVENESS OF INFRASTRUCTURE DEVELOPMENT FOR WASTEWATER SERVICE IN DECENTRALIZED INDONESIA: CASE OF BANDUNG MUNICIPALITY - Diny Waskitawati; Ida Widianingsih; Budhi Gunawan (Diponegoro University, 2019)
This paper discusses the effectiveness of infrastructure development for wastewater service in decentralized Indonesia, particularly in Bandung municipality as one of the biggest cities in the country where sanitation problems persist. Although wastewater service coverage in Bandung municipality shows a gradual improvement from 2010 to 2016, the research identifies the ineffectiveness of wastewater infrastructure development. Qualitative analyses revealed that the wastewater infrastructure development in Bandung municipality funds came from two different sources (local budget and internal donor support). We would argue that in the case of wastewater infrastructure development, the same amount of money shares different processes and results. Compared to AusAID water and sanitation program, in term of value of money, the one designed and managed by the Municipality Water Supply Agency (PDAMs) is less effective. It is concluded the newly developed decentralization laws in Indonesia could not ensure the effectiveness of public service delivery due to the absence of sound governance at local level.